MARTIN HEIDEGGER’S METAPHYSICAL QUESTION 1935-1937: GENESIS AND CONSEQUENCES. PART ONE - Юрій МАРИНЧУК (Епістемологічні дослідження у філософії, соціальних і політичних науках)
The article deals with the subject of poetic language, its qualities, conditions and purpose. It is the language of creativity and sets out the metaphysics in art. The metaphysics considered is the intersection of being and time in thing and thing as a special place where thoughts appear in the artistic act. The first plan of the stated metaphysics is considered in the fourfold geometric intersection of the essential-artistic space – the square (Gefirt) of the world, earth, mortals and immortals. The result of the semantic field of landscape from our memory of native lands is a history of the meanings of thinking, and things are pre-thought states. A thing is the way the world is given - a narrative of the structure of thinking, life and human activity. The second plan of the stated metaphysics is considered, on the one hand, from the position of poets and oracles, as those who express themselves historically, and, on the other hand, from the inner basis of thinking. This foundation is intuitive, affective-intellectual thought. It emerges in the circle of unknown, unexplored, impossible things – in the topos, where the world of life is formed by co-existence with what we enter into, creating meaning for ourselves. Co-existence means examining the thing for the interruption of being and time and what information about the world can be extracted. But it turns out that there is no being at all and no time at all, for there are no two things of one thing: that which belongs to being and that which belongs to time. It turns out that the intersection is thinking. It builds meaningful forms, lives them and carries them in language. To a certain extent, the thinking we possess is seen as a device of time. Martin Heidegger, through the existential Care, arranges thinking by the relation of being and time in a thing. He draws our attention to the fact that not only man owes his truth to the co-existence of life, but also the thing with its nature. The purpose of this article is to investigate the foundations of poetic language of creation as a way of presentation of metaphysics in art.